Clinical validity of clinical treatment score 5 (CTS5) for estimating risk of late recurrence in unselected, non-trial patients with early oestrogen receptor-positive breast cancer - Richman, Juliet (Breast Cancer Res Treat, 2020)
ABSTRACT: PURPOSE: Clinical Treatment Score at 5 years (CTS5) is a prognostic tool to estimate distant recurrence (DR) risk after 5 years of endocrine therapy for postmenopausal women with oestrogen receptor-positive (ER-positive) breast cancer. METHODS: The validity of CTS5 was tested in a retrospective cohort of patients diagnosed with early ER-positive breast cancer. The primary endpoint was DR in years 5–10. The primary analysis cohort consisted of postmenopausal women, with premenopausal women as a secondary analysis cohort. Cox regression models were used to determine the prognostic value of CTS5 and Kaplan–Meier curves were used with associated 10-year DR risks (%). RESULTS: 2428 women were included with a median follow-up of 13.4 years. The CTS5 was significantly prognostic in both postmenopausal (N = 1662, HR = 2.18 95% CI (1.78–2.67)) and premenopausal women (N = 766, HR = 1.84 95% CI (1.32–2.56)). The 10-year DR risks were 2.9% (1.9–4.5), 7.2% (5.3–9.9), and 12.9% (10.0–16.7) for low, intermediate and high risk in postmenopausal women and 3.8% (2.2–6.7), 6.9% (4.4–10.8), and 11.1% (7.4–16.5) in premenopausal women, respectively. The number of observed DRs was significantly greater than expected in those predicted to be at high risk by CTS5 but this discordance was lost when those receiving more than 60 months of endocrine therapy were excluded. CONCLUSIONS: The CTS5 demonstrated clinical validity for predicting late DR within a large cohort of unselected postmenopausal patients but less so in premenopausal patients. Calibration of the CTS5 was good in patients who did not receive extended endocrine therapy. The CTS5 low-risk cohort has risk of DR so low as to not warrant extended endocrine therapy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10549-020-06013-6) contains supplementary material, which is available to authorized users.